PENYERTAAN AKADWAKALAH PADA PEMBIAYAAN MURABAHAH (Studi Di BNI Syariah Cabang Kendari) - Kalsum, Ummi; Saputra, Eka Rizky (Institut Agama Islam Negeri Kendari, 2016)
Abstract Inclusion wakalah in murabaha financing is an innovative banking practitioners, hybrid contract, an agreement the two parties to implement a contract that contains two or more contract. Wakalah wal Murabahah is a financing agreement of sale and purchase, the bank as the seller has set aside and delegate to the customer as a buyer to purchase their own items needed on behalf of a third party bank independently. This study aims to determine the implementation of inclusion wakalah on murabaha financing at BNI Syariah Branch Kendari and economic overview of Islam against the inclusion of such contract. This study is a qualitative research using interview, observation and documentation to collect data, and then processed and analyzed by the reduction step, presentation and conclusion. Based on the nature and purpose, this study included descriptive exploratory study. The approach used in this study is normative. Based on the results of the study found a discrepancy between the implementation of inclusion wakalah on murabaha financing at BNI Syariah Branch Kendari with a scheme provided by the bank. First, themurabaha contract which should be done after the customer as the representative of the bank buys the goods to the supplier turned out to be held in conjunction with wakalah. Second, purchasing goods over to the customer representative was not in the name but in the name of customers bank itself. Third, funding the purchase of goods that should be paid directly by the bank to the supplier turned out to be melted first by transferring to customers' accounts.In the perspective of Islamic economics, murabaha wal wakalah included in this type of merger contract are allowed, but each pillar and second terms in this contract must be fulfilled if it will be combined. However, in practice, the financing murabaha wal wakalah happened in BNI Syariah Branch Kendari has invalidated one of the pillars and the terms of the sale and purchase namely the lack of traded goods and the goods are not the full property rights berakad parties. Offers to buy this kind of forbidden because included in the category of selling goods that are not owned, sell goods that is not your own and set a profit on goods that are not yet under control. Terms in wakalah also not fulfilled because the goods to be purchased has not become the property of the bank. The bank does not have a relationship of cooperation and agreement in the purchase agreements with suppliers of goods so that the purchasing process can not be delegated to the customer. Keywords: Inclusion, wakalah, murabaha financing, and BNI Syariah Branch Kendari